Intraosseous Catheter Flow Rates and Ease of Placement at Various Sites in Canine Cadavers - Lange, James; Boysen, Søren R.; Bentley, Adam; Atilla, Aylin (Frontiers in Veterinary Science, 2019)
Abstract Objective – To compare intraosseous catheter placement difficulty, success rates, and flow rates at four different locations in canine cadavers. Design – Prospective study. Setting – Private referral centre. Animals - Fresh canine cadavers. Interventions – With owner consent, animals presenting for euthanasia were recruited. Animals received heparin (1000IU/kg IV) at least five minutes prior to euthanasia. After euthanasia, EZIO intraosseous catheters were placed into the ilial wing, proximal medial tibia, proximal lateral humerus and distal lateral femur on one side of the animal. Time to catheter placement and catheter difficulty were scored for each placement site. Sterile saline was infused into each location simultaneously over five minutes, first via gravity then using 300mmHg pressure. Animals were repositioned onto the contra-lateral side and the experiment repeated. Measurements and Main Results – Placement was successful in 16/22 ilial, 18/22 tibial, and 22/22 femoral and humoral attempts. A post hoc analysis revealed the ileum had a significantly greater difficulty score when compared to the femur and humerus (p ≤ 0.0001). There was a statistically significant difference in placement time between the femur and the ileum (p ≤ 0.05). Gravity infusion rates in the tibia were statistically lower than the humerus (p≤0.01) and between the tibia and the femur (p ≤0.001). Additionally, pressurized infusion rates were statistically lower in the tibia compared to the humerus (p ≤0.0001), the femur (p ≤0.0001) and the ileum (p ≤0.01). Conclusions – The femur and humerus had high success rate for IO catheter placement and low placement time and difficulty scores. Pressurized intraosseous flow rates were highest in the humerus and femur. Contrary to human literature, success rates for catheter placement in the humerus and femur were higher than at other sites, suggesting the humerus and femur may be preferred sites for intraosseous catheter placement in the dog. Further investigation through a larger sample size is required to confirm these findings.